SPIRITUALITY IN LEADERSHIP. RESEARCH INTO SCHOOLS, CONGREGATIONS AND THE WORKPLACE - C.A.M. Hermans (Acta Theologica)
What drives leaders to inspire, orientate and motivate members in organisations such as schools, congregations, and parachurch organisations, and to transform social life forms? We need leaders who transform organisations and society at large; who are authentic and a moral example; who know how to discern in view of the interest of the people they serve; who are transformed themselves from the cultural and power-related forces of history as, for example, in South Africa that struggles with issues of injustice and reconciliation. Transformative, authentic or servant leadership is highly valued, but there is a lack of knowledge as to how to develop or educate leaders in this way. The question of theory development centres around the concept of spirituality. Different disciplines such as management sciences, psychology, education, and business ethics study the concept of spirituality in relation to leadership. This special issue aims to contribute to this theory-building from the perspective of practical theology and religious studies.